Transformation in industrial specialisation and features of economic development across the subjects of the Russian Federation - Antonyuk, Valentina; Vansovich, Elmira; Lapo, Anastasiya (Journal of new economy, 2020)
Crisis phenomena in Russia stimulate interest in researching the influence of regions’ industrial specialisation on the rates and trajectories of their economic development. The paper aims to examine the transformation of industrial specialisation across the Russian regions and correlate it with their economic development. The methodological basis of the study rests on the theoretical concepts of regional and spatial economics, systems analysis, and strategic management. The authors monitor the changes in the industrial specialisation across the subjects of the Russian Federation in 2008–2016, as well as the dynamics of their economic development by using a combination of methods: dialectical, causal, comparative, structural and cluster analysis. The paper identifies the strategic challenges and priority areas for the modern development of the regions of the Russian Federation. Based on the analysis of the economy of 61 subjects of the Russian Federation, the authors draw conclusions on the transformation of regional industrial specialisation in a specific type of economic activity; on the relationship between economic development and the nature of specialisation (mono-specialisation, multi-specialisation); on the dynamics of developed regions among the groups of mono-specialised and multi-specialised ones. The study detects the types of economic activity, which affect economic development the most. The analysis of the dynamics of industrial specialisation results in the conclusion that there are regions with stable and unstable specialisation. The article proposes promising directions of the state structural policy for different types of regions. The theoretical and practical significance of the study lies in the fact that the developed method allows not only evaluating the transformations in the industrial specialisation of the regions, but also correlating them with the economic development of the subjects of the Russian Federation.